TSC2 regulates lysosome biogenesis via a non-canonical RAGC and TFEB-dependent mechanism - Nicola Alesi (Nature Portfolio, 2021)
Tuberous sclerosis complex (TSC) is a multiorgan disease that can lead to hyperactive mTORC1 due to deficient TSC1 or TSC2 protein function. Here, the authors find that despite high mTORC1 activity, TFEB localizes to the nucleus and drives lysosomal gene expression via a non-canonical Rag-dependent mechanism.